Peran Generasi Muda dalam Pengembangan Ekonomi Islam Era Digital - Meli Amelia; Sitri Sitri; Gama Pratama (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The digital era has significantly impacted various sectors of life, including the development of the Islamic economy. Young people, as the majority of digital technology users, hold a strategic role in accelerating the growth and advancement of Islamic economics. This study aims to analyze the role of youth in driving the transformation of Islamic economics in the digital era, particularly through technological financial innovations (Islamic fintech), Islamic economic literacy, and the utilization of social media as a medium for education and halal product promotion. This research employs a qualitative method with a literature review approach, examining relevant references from journals, books, and recent digital sources. The findings reveal that youth are not only consumers but also innovators, entrepreneurs, and change agents in advancing the Islamic economy. Their involvement in Sharia-based start-ups, halal e-commerce, and the digitalization of zakat, infaq, sadaqah, and waqf (ZISWAF) provides concrete evidence of their contribution. In conclusion, youth serve as the key driver in the acceleration of digital-based Islamic economics, provided that their roles are supported by improved literacy, adequate regulations, and an inclusive digital ecosystem.